The Perception of Waqf (Endowment) in Indonesian Society: Exploring the Dynamics of Sale, Exchange, and Legal Understanding - Wahyudi Sarju Abdurrahim; Syamsul Hadi; Khotibul Umam (Journal Of Social Science (JoSS), 2025)
This study explores the multifaceted perceptions of Waqf (Islamic endowment) within Indonesian society, examining its understanding as a form of perpetual charity (amal jariyah), its relationship with general alms (sadaqah), and its traditional limitation to physical assets. It further investigates the implications of a limited legal understanding on Waqf management and development. Employing a qualitative, descriptive-analytical approach, this research is based on a comprehensive literature review. Data were gathered from scholarly articles, institutional reports, legal documents (notably Law No. 41 of 2004), and Islamic primary sources, and analyzed thematically. The study reveals that while Waqf is strongly perceived as amal jariyah, providing significant spiritual motivation, public understanding often remains simplistic. Waqf is frequently conflated with general sadaqah, and its scope is predominantly viewed as limited to immovable assets like land and buildings. This is coupled with a widespread lack of literacy regarding the legal pillars of Waqf, the potential of productive and cash Waqf, and the regulatory framework, leading to challenges in management, underutilization of assets, and risks of misuse. The findings indicate a critical gap between spiritual intent and comprehensive legal-economic understanding. Enhancing systematic public education, clarifying distinctions between Waqf and other charitable forms, promoting non-physical Waqf models, and strengthening legal socialization are essential to optimize Waqf’s role as a sustainable instrument for socio-economic development in Indonesia